Distribution, Temporal Change, and Conservation Status of Tropical Seagrass Beds in Southeast Asia: 2000–2020 - Sudo, Kenji; Quiros, T. E. Angela L.; Prathep, Anchana; Luong, Cao Van; Lin, Hsing-Juh; Bujang, Japar Sidik; Ooi, Jillian Lean Sim; Fortes, Miguel D.; Zakaria, Muta Harah; Yaakub, Siti Maryam; Tan, Yi Mei; Huang, Xiaoping; et al. (Frontiers in Marine Science, 2021)
Although Southeast Asia is a hotspot of global seagrass diversity, there have been great information gaps in the distribution of seagrass beds. Information on broad-scale distribution has not been updated in a global database since the late 1990s although studies on seagrasses have been undertaken intensively in each region. Here we analyzed the recent distribution of tropical seagrass beds, their temporal changes, causes of decline and conservation status in Southeast Asia (plus southern Mainland China, Taiwan and Ryukyu Island of Japan) using data collected after 2000. Based on the 196 literature published since 2000, we identified 1261 point data and 1461 polygon data showing the distribution of seagrass beds. A large discrepancy was found in the seagrass bed distribution between our updated data and UNEP-WCMC published in 2001, mostly due to inaccurate and low resolution location information in the latter. Temporal changes in seagrass bed area, analyzed for 68 sites in 9 countries/regions demonstrated that more than half of the seagrass beds declined with the average rate of 10.9% yr-1 since the late 1990s. Various types of human-induced threats were reported as causes for the decline, including coastal development, fisheries/aquaculture and natural factors such as typhoons and tsunamis. The percentage of seagrass beds covered with existing MPAs varied greatly among countries/regions, from less than 1% in Brunei Darussalam and Singapore to 100% in southern Japan. However, the degree of conservation regulation was not sufficient even in regions with higher MPA coverage. The proportion covered with EBSAs (Ecologically and Biologically Significant Area determined by the Convention of Biological Diversity) was higher than areas within MPAs, indicating that inclusion of EBSAs to MPAs can greatly improve the conservation status of seagrass beds in this region.